Konsep Zikir dalam Tarekat Qadiriyah Naqsabandiyah dan Implikasinya terhadap Pembentukan Kepribadian Spiritual : The Concept of Zikr in the Qadiriyah Naqshbandiyah Order and Its Implications for the Formation of Spiritual Character - Ardianto Ardianto; Muhammad Husnur Rofiq; Ismawati Ismawati; Nor Mubin; Moh. Syahru Romadhan (Institut Agama Islam Daruttaqwa Gresik, 2026)
The phenomenon of spiritual crisis and the increasing prevalence of psychological disorders in modern life highlights the need for approaches that integrate religious and psychological dimensions comprehensively. The practice of dhikr (remembrance of God) in the Sufi tradition, particularly within the Qadiriyah Naqshbandiyah Order (TQN), is considered a potential method for developing spiritual personality while enhancing individual mental well-being. However, studies that specifically elaborate the mechanism of dhikr in TQN as a process of spiritual personality formation remain limited. This study aims to analyze the concept of dhikr in the Qadiriyah Naqshbandiyah Order and examine its implications for the formation of spiritual personality. The research employs a qualitative approach using a library research method, drawing on classical and contemporary literature related to Sufism, tariqa traditions, and spiritual psychology. The findings indicate that dhikr in TQN is not merely a verbal activity but a process of internalizing tawhidic values encompassing cognitive, affective, and behavioral dimensions. Practices such as loud dhikr (jahr), silent dhikr (khafi), rabitah, and riyadhah significantly contribute to the development of spiritual personality, characterized by inner peace, emotional regulation, heightened God-consciousness, and the cultivation of moral virtues. The implications of this study suggest that dhikr in TQN can be positioned not only as a form of worship but also as a psychospiritual approach relevant to mental health development and holistic character formation.